Apps-Based Temperature Monitoring System with Location Services for Medical Needs Delivery Using Drone - Gan, Kok Beng; Mohd, Syahril Amir; Ng, Tze Yee (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Traditional temperature monitoring system for blood delivery requires a USB cable to extract data after delivery has been completed. Without real-time temperature data during delivery, the quality of the products cannot be monitored efficiently. In this paper, we have designed and developed a mobile application-based temperature monitoring system for medical needs delivery. It has a mobile application to display temperature data in real-time. The system includes Arduino Uno, DHT22, DS3231, microSD card adapter and ESP8266 Wi-Fi module. The temperature and humidity data were stored in the microSD card and ThingSpeak server for further analysis. A mobile application allowed users to visualized and monitor the temperature of the payload during delivery. For the system test and evaluation purpose, the developed temperature monitoring system was placed inside a polystyrene box. The temperature and humidity data were acquired using DHT22 and Fluke t3000 fc in cold and ambient temperature for 30 minutes with a sampling time of 2 seconds in the polystyrene box. The results showed that the correlations error 0.96 and 1.00, respectively. Finally, we showed that the developed temperature monitoring system can capture and record temperature data in real-time. It is reliable and comparable to a high-end temperature monitor.